Global sagittal spinal alignment at cervical flexion in patients with dropped head syndrome. (27th August 2020) - Konishi, Takamitsu; Endo, Kenji; Aihara, Takato; Suzuki, Hidekazu; Matsuoka, Yuji; Nishimura, Hirosuke; Takamatsu, Taichiro; Murata, Kazuma; Kusakabe, Takuya; Maekawa, Asato; Sawaji, Yasunobu; Yamamoto, Kengo
Purpose: Dropped head syndrome (DHS) is characterized by the passively correctable chin-on-chest deformity. The characteristic feature is emphasized in the cervical flexion position. The purpose of this study was to analyze the influence of cervical flexion on sagittal spinal alignment in patients with DHS. Methods: The study included 15 DHS subjects and 55 cervical spondylosis (CS) subjects as the control group. The following parameters were analyzed: cervical sagittal vertical axis (C-SVA), occipitoaxial angle (O–C2A), C2 slope (C2S), C2–C7 angle (C2–C7A), T1 slope (T1S), sagittal vertical axis, T1–T4 angle (T1–T4A), T5–T8 angle (T5–T8A), T9–T12 angle, lumbar lordosis, sacral slope, and pelvic tilt, in cervical flexion and neutral positions. Results: The values of C-SVA, O–C2A, C2S, and T1S were significantly different between CS and DHS at cervical neutral and flexion positions. C2–C7A showed significant difference in cervical neutral position, but the difference disappeared in flexion position. T1–T4A did not present a significant difference, but T5–T8A showed a difference in neutral and flexion positions. Conclusions: Malalignment of DHS extended not only to cervical spine but also to cranio-cervical junction and thoracic spine, except T1–T4. It is known that global sagittal spinal alignment is correlated with adjacent parameters, although in DHS the reciprocal change was lost from cranio-cervical junction to the middle part of thoracic spine at cervical flexion.